2014
DOI: 10.1111/1753-6405.12163
|View full text |Cite
|
Sign up to set email alerts
|

Are they protected? Immunity to vaccine‐preventable diseases in healthcare workers at an Australian hospital

Abstract: Objective: Australian guidelines for healthcare worker (HCW) vaccination were updated in 2010, and pre-employment assessment of new employees has previously been identified as a priority. We determined the vaccination status of a cohort of existing HCWs at a tertiary hospital in Melbourne, Victoria.Methods: Random sampling of HCWs employed prior to 2006 with unknown/incomplete immunisation status was conducted between April and August 2011. Immunity to vaccinepreventable diseases (VPDs) was determined serologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
1
9
1
Order By: Relevance
“…Compared with the international literature, we found similar rates of seropositivity for measles, mumps, VZV and HBV. However, the rates of seropositivity for rubella were considerably lower in our studied population of HCWs (78%) than have been reported with other recent Australian 11,13 and international 7–10 studies (seropositivity rates range from 83% to 91%). Vagholkar and colleagues found 91% of HCWs were seropositive to measles, 89% for mumps, 91% for rubella, 89% to VZV and only 64% for HBV 11 .…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Compared with the international literature, we found similar rates of seropositivity for measles, mumps, VZV and HBV. However, the rates of seropositivity for rubella were considerably lower in our studied population of HCWs (78%) than have been reported with other recent Australian 11,13 and international 7–10 studies (seropositivity rates range from 83% to 91%). Vagholkar and colleagues found 91% of HCWs were seropositive to measles, 89% for mumps, 91% for rubella, 89% to VZV and only 64% for HBV 11 .…”
Section: Discussioncontrasting
confidence: 79%
“…Vagholkar and colleagues found 91% of HCWs were seropositive to measles, 89% for mumps, 91% for rubella, 89% to VZV and only 64% for HBV 11 . More recently, Leung and colleagues performed a smaller study and showed rates of seroprotection of 92% for measles, 80% for mumps, 86% for rubella, 98% for VZV and 82% for HBV 13 . The reasons for the discrepancies seen between our results and the other Australian studies are unclear, but could relate to the laboratory cut‐off used for positive versus equivocal serology results, smaller study size in previous studies, differences in populations included and demographic factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] Despite this, HCW uptake of recommended vaccines is low 2,[8][9][10][11][12][13][14][15][16] , particularly for seasonal influenza and pertussis. 13,[16][17][18][19] In Australia, both pertussis and seasonal influenza vaccines are recommended for all HCWs 17 however providing free influenza vaccine is a policy decision for each hospital or state and is not uniform across Australia. 20 Influenza virus infection causes a wide spectrum of disease, from no or minimal symptoms, to respiratory illness with systemic features, and/or multisystem complications and death from primary viral or secondary bacterial pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…22 HCWs have a higher risk of exposure to pertussis due to occupational contact and may be asymptomatic, acting as a reservoir to vulnerable patients in their care. [23][24][25] With low uptake of pertussis vaccine among HCWs 13,18,26 nosocomial outbreaks have been reported. 4,[27][28][29][30][31] In the workplace environment, it is plausible that vaccination recommendations and practices for some vaccinations may influence the uptake of other vaccines.…”
Section: Introductionmentioning
confidence: 99%